PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KOMPETENSI PENGELOLAAN KELAS DI SEKOLAH DASAR KRISTEN YSKI SEMARANG - Wahono . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
Manage the class can success if worked by professional teacher. Professional teacher to own competency manage the class that to shape some skill. Professional teacher have to be able respond mutation in the society includes manage the class. The case at the public school like as teacher at SD Kristen YSKI Semarang.Problem in the research formulated to become tree point is how much big (1) Influence work motivation to the competency manage the class, (2) Influence climate organization to the competency manage the class, and (3) influence work motivation and climate organization to the competency manage the class by teacher SD Kristen YSKI Semarang.The subject of research is teacher SD Kristen YSKI Semarang to the number of 104 peoples. The Sample of research to fix to the number 55 respondents, the Variable of research is competency manage the class, motivation teacher work, and climate organization school. The model to collect data used questioner is to the test validity and reliability. Analysis data used analysis double regression.Test hypothesis used test F.Proceeds of research founded influence that significant at : (1) work motivation teacher to the competency manage the class by teacher SD Kristen YSKI Semarang with coefficient correlation partial 0,471 (22,18%); (2) climate organization to the competency manage the class teacher SDKristen YSKI Semarang with coefficient correlation partial 0,293 (8,58%); (3) work motivation teacher and climate organization to the competency manage the class by teacher SD Kristen YSKI Semarang with coefficient correlation double as 0,596 (35,5%).Based on this proceed of research, management SD Kristen YSKI Semarang preferably (1) Increase work motivation for teacher and staff. The case can do with give to appreciation for teacher which performance, opportunity to propagate potency, bonus concordant capability, (2) to watch and to advance climate organization. The case can reach with to advance to be able manager,trust, to build up communication, coordination with teacher and staff to make decision, to grow felling useful, responsibility, give bonus fairly.